2012
DOI: 10.1021/ef300531r
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Physical and Chemical Properties of Alternative Fuels on Combustion, Gaseous Emissions, and Particulate Matter during Steady and Transient Engine Operation

Abstract: Properties of alternative fuels, such as cetane number, aromatic content, bulk modulus, etc., can vary significantly; thus, a detailed investigation is conducted to assess the impacts on engine combustion, efficiency, and emissions during steady-state and transient engine conditions. Insights can be used to maximize the benefits of alternative fuels or to avoid potential problems that stem from differing ignition and combustion characteristics of particular fuels. In this work, biodiesel (20%, 50%, and 100% bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Differences in fuel can have a significant effect on cdPM properties, including size distribution, surface area, ability to generate reactive oxygen species, and volatile content. [1013]…”
Section: Introductionmentioning
confidence: 99%
“…Differences in fuel can have a significant effect on cdPM properties, including size distribution, surface area, ability to generate reactive oxygen species, and volatile content. [1013]…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [15] observed that the viscosity of oxygenated fuels influenced spray atomization behavior. Other experimental comparisons have been made to assess the sensitivity of engine performance, emissions, and spray characteristics to the properties of alternative diesel fuels, such as dimethyl ether (DME), biodiesel, and jet fuel, which are significantly different from those of petroleum derived diesel fuel [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The different physicochemical properties of blended fuels could in turn affect the fuel injection and combustion process, and thus probably lead to major differences in DPM properties and their toxicity. 14 However, no systematic study has been conducted to make a comparative evaluation of fundamental changes in the physicochemical characteristics of particulate emissions resulting from the combustion of diesel blended with several oxygenates with different thermophysical properties and to relate these changes to the toxicity of particulates in an integrated manner, to the best of our knowledge.…”
Section: ■ Introductionmentioning
confidence: 99%